The effect on thrombin generation and anti-Xa levels of thromboprophylaxis dose adjustment in post-cesarean obese patients - A prospective cohort study. Issue 170 (October 2018) - Rottenstreich, Amihai; Levin, Gabriel; Elchalal, Uriel; Kleinstern, Geffen; Spectre, Galia; Ziv, Esther; Yagel, Simcha; Kalish, Yosef
Abstract: Objective: To examine the laboratory anticoagulant effect of two thromboprophylactic low-molecular weight heparin (LMWH) regimens in post-cesarean obese patients. Methods: A prospective cohort study, performed during 2017–2018 at a university hospital, of post-cesarean obese (>90 kg) patients receiving 40 mg/day ( n = 30) or 60 mg/day ( n = 30) enoxaparin, and a control group of non-obese ( n = 30) post-cesarean patients receiving 40 mg/day enoxaparin. Thrombin generation and anti-Xa were measured twice on the third postoperative day: prior to and 3.5–4 h following the third LMWH dose. Results: Age, parity, weight and body mass index were comparable between the obese study groups. Compared to the control non-obese group, the 40 mg obese and 60 mg obese groups showed increased baseline thrombin generation: medians 491, 581, 571 nM, respectively ( P = 0.001 and P = 0.04, respectively). At peak LMWH activity, thrombin generation was higher in the 40 mg than in the 60 mg obese and control groups: medians 2599, 2391, 2229 nM, respectively ( P = 0.01 and P < 0.0001, respectively); and thrombin generation was comparable between the 60 mg obese and the control groups ( P = 0.58). Similarly, a significantly lower proportion of patients in the 40 mg obese group (10%) had anti-Xa levels within the recommended prophylactic range (0.2–0.5 IU/mL) than in the other groups ( P < 0.0001 for both comparisons). Conclusion: As determined by thrombin generation and anti-Xa testing, post-cesarean obese patients have an increased procoagulant potential, which was diminished only in those receiving higher dosages of LMWH. These findings support the need for clinical evaluation of LMWH dose adjustment in this setting. Highlights: A prospective study of 2 LMWH regimens in post-cesarean obese women. Thrombin generation and anti-Xa levels were assessed. Procoagulant potential was higher in post-cesarean obese women than in controls. This was diminished only in those receiving higher LMWH dosage (60 vs. 40 mg/day). Clinical evaluation of LMWH dose adjustment in postpartum obese patients is needed.